2022
DOI: 10.21037/jtd-21-1285
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality 3D navigation system for percutaneous CT-guided pulmonary ground-glass opacity biopsies: a comparison with the standard CT-guided technique

Abstract: Background: Augmented reality navigation system for percutaneous computed tomography (CT)-guided pulmonary biopsies has recently been introduced. There are no studies in literature about its use for ground glass lesions biopsies. The aim of this study is to evaluate the effectiveness of an augmented reality infrared navigation system performance on CT-guided percutaneous lung ground glass opacity (GGO) biopsy compared to a standard CT-guided technique.Methods: A total of 80 patients with lung GGO who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Recently, an augmented reality navigation system has been introduced for percutaneous CT-guided pulmonary GGO biopsies. Faiella et al reported that this system can increase the diagnostic success rate for GGO lesions < 1.5 cm [15].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, an augmented reality navigation system has been introduced for percutaneous CT-guided pulmonary GGO biopsies. Faiella et al reported that this system can increase the diagnostic success rate for GGO lesions < 1.5 cm [15].…”
Section: Discussionmentioning
confidence: 98%
“…75 Touchless interaction is another AI function which has been examined, it enables the physician to give commands while under sterile conditions, such as activating lights, switching on and off components of medical devices, or even using hand and arm gestures to browse through sets of medical images without touch. 76,77 Lastly, augmented reality (AR) and virtual reality (VR) could assist during IO procedures. While VR is mostly studied for teaching purposes, AR is experimented with in clinical practice for assistance during liver ablation and pulmonary biopsies.…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
“…[78][79][80] Specifically for pulmonary ground glass opacities, AR-assisted biopsies showed higher diagnostic accuracy for nodules <1.5 cm, a lower incidence in complications and a significant reduction of the administered radiation dose, compared to standard biopsies. 77 For patient classification and outcome prediction, studies frequently combine AI with radiomics. Radiomics is the field wherein medical images are converted into quantitative data that can be analysed using AI methods to determine the relationship between medical images and clinical outcomes.…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern of CT guidance is the radiation dose to the interventional radiologist and the patients [ 70 ] even if some studies reported values in line with recommended dose limits for occupational radiation exposure [ 71 ]. To reduce the time needed for placing the probe/needle and therefore the radiation dose, some navigation systems have been developed to assist lung biopsies and thermal ablation therapies, and studies demonstrated that CT assisted with stereotactic navigation reduces the time for ablation probe placement, the number of needle adjustments, skin punctures, and fluoroscopy time [ 72 , 73 ]. The disadvantages of CT-guided procedures are the lack of tumor visibility on unenhanced images or, in the case of contrast media administration, the short contrast-enhancement timeframe [ 74 , 75 ].…”
Section: Imaging Modalitiesmentioning
confidence: 99%